PENGARUH QUALITY OF WORK LIFE DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP EMPLOYEE ENGAGEMENT PADA KARYAWAN CV. X CABANG KABUPATEN TULUNGAGUNG DAN BLITAR - Agil Rizki Nugroho; Widjajaning Budi; Bachtiar Susanto (Jurnal Psikologi Poseidon, 2018)
Human resources have an important role as the driving wheel of the company in order to achieve a goal owned by the company. Therefore, to achieve the objectives of the company then it takes human resources that are proactive, have initiative, responsible and have high performance standards and also dedicated, in other words the company requires an employee who is engaged. The purpose of this research is to know the influence of quality of work life and transformational leadership style together to employee engagement on employee CV. X Branches Tulungagung and Blitar districts. Hypothesis proposed in this research is There is influence of quality of work life and transformational leadership style to employee engagement at employee CV. X Branches Tulungagung and Blitar districts. The population in this study amounted to 43 people, with a total sample of 37 people. Sampling technique in this research is by purposive sampling technique. Where Purposive Sampling is a technique of determining the sample with a particular consideration that is owned by the researcher. Based on the value of significance in the anova table is 0.000 is less than 0,05 so it can be concluded that the value of regression coefficient is significant (significant model) which means together independent variable that is quality of work life (X1) and transformational leadership (X2) have influence Which is significant to the dependent variable that is employee engagement (Y). Based on the summary table can be seen that the value of R Square shows 0.687. Thus it can be seen that the magnitude of influence variable quality of work life and transformational leadership together to employee engagement is equal to 68.7%. In other words, the hypothesis in this study is accepted.